2016
DOI: 10.3803/enm.2016.31.4.586
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Diagnosis Using Residual Liquid-Based Cytology Materials for Patients with Nondiagnostic or Indeterminate Thyroid Nodules

Abstract: BackgroundMolecular analysis for common somatic mutations in thyroid cancer can improve diagnostic accuracy of fine-needle aspiration cytology (FNAC) in the nondiagnostic or indeterminate category of thyroid nodules. In this study, we evaluated the feasibility of molecular diagnosis from residual liquid-based cytology (LBC) material after cytological diagnosis.MethodsThis prospective study enrolled 53 patients with thyroid nodules diagnosed as nondiagnostic, atypia of undetermined significance (AUS), or follic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 35 publications
(62 reference statements)
1
12
0
1
Order By: Relevance
“…Recent studies have reported on the feasibility of using residual liquid‐based cytology from thyroid FNA samples to perform molecular testing; this is akin to human papillomavirus testing from residual liquid‐based cytology in cervical cytology samples . A recent study has reported the detection of BRAF mutations by pyrosequencing in a subset of supernatants from FNA centrifuged needle rinses of thyroid nodules .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have reported on the feasibility of using residual liquid‐based cytology from thyroid FNA samples to perform molecular testing; this is akin to human papillomavirus testing from residual liquid‐based cytology in cervical cytology samples . A recent study has reported the detection of BRAF mutations by pyrosequencing in a subset of supernatants from FNA centrifuged needle rinses of thyroid nodules .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have explored the usefulness of the molecular testing of residual LBC from nongynecological FNA samples, with promising results. Several studies have been published to date describing the usefulness of extracting nucleic acids from residual LBC solution from thyroid FNA specimens for mutation analysis using high‐resolution melting polymerase chain reaction (PCR), pyrosequencing, and next‐generation sequencing (NGS), and evaluating gene rearrangements using quantitative PCR . Wei et al described using residual PreservCyt (Cytyc Corporation, Marlborough, Massachusetts) specimens from FNA samples and body fluids (either fresh unconcentrated specimens or residual PreservCyt specimens) to extract DNA for multigene NGS analysis .…”
mentioning
confidence: 99%
“…Extraction kits vary in the input amount, extraction volume, and chemistry used, and differing results in terms of the quantity and type of DNA extracted among studies that use different kits are to be expected. 29 Studies in which nucleic acid was analyzed after extraction from thyroid FNA needle rinses are listed in Table 5, 10,18,20,23,25,30 along with their respective nucleic acid extraction kits and associated methodologies, all of which used manual processing. Among the studies, only one 18 used the same extraction kit as that in the current study, and the authors reported neither the quantity nor the quality of nucleic acids extracted.…”
Section: Nucleic Acid Extractionmentioning
confidence: 99%
“…In a study that used an ethanol-based fixative with a small (<0.2%) concentration of formalin (SurePath; Becton Dickinson and Company), Kwon et al reported an elevated rate of p.Val600Glu mutations in the BRAF gene in TBSRTC category III specimens compared with the current study. 30 This suggests discrepant morphologic diagnoses between the 2 studies, which may be mitigated by careful monitoring of diagnostic AUS rates and AUS:malignant ratios. 31 It is also important to establish the lower limit of tumor cellularity at which genetic alterations may be detected with confidence.…”
Section: Other Preanalytic Variablesmentioning
confidence: 99%